2017
DOI: 10.1038/s41598-017-10536-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel chiral stationary phase LC-MS/MS method to evaluate oxidation mechanisms of edible oils

Abstract: The elucidation of lipid oxidation mechanisms of food is vital. In certain lipids, characteristic lipid hydroperoxide isomers are formed by different oxidation mechanisms (i.e., photo-oxidation or auto-oxidation). For example, linoleic acid is photo-oxidized to 13-9Z, 11E-hydroperoxyoctadecadienoic acid (HPODE), 12-9Z,13E-HPODE, 10-8E,12Z-HPODE and 9-10E,12Z-HPODE, whereas 13-9Z, 11E-HPODE, 13-9E,11E-HPODE, 9-10E,12Z-HPODE and 9-10E,12E-HPODE are formed by auto-oxidation. Therefore, we considered that oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 34 publications
2
37
0
1
Order By: Relevance
“…values observed for vegetable oils 1–8 with the k s ( f ) (Calcd.) values calculated using the rate constants (ksAOHi()f) and the concentrations ([AOH‐ i ]) of each AOH included in vegetable oils 1–8, measurements of the concentrations (in mg 100 g −1 ) of four Tocs and four Toc‐3s were performed (Ito et al, ; Mukai et al, ). The results obtained are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…values observed for vegetable oils 1–8 with the k s ( f ) (Calcd.) values calculated using the rate constants (ksAOHi()f) and the concentrations ([AOH‐ i ]) of each AOH included in vegetable oils 1–8, measurements of the concentrations (in mg 100 g −1 ) of four Tocs and four Toc‐3s were performed (Ito et al, ; Mukai et al, ). The results obtained are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations of α‐, β‐, γ‐, and δ‐Tocs and ‐Toc‐3s in vegetable oils 1–8 were determined using HPLC–MS/MS, as reported in a previous study (Ito et al, ). Briefly, 100 mg of edible oil was weighed and dissolved in 2 mL of n ‐hexane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, first, concentrations of nine fatty acids 1 -9 i.e., Acid-i i 1 -9 contained in vegetable oils 1 -8 were determined, via gas chromatography GC 34,35 . Second, measurements of the rate constants k Q LH S and k Q LH t 1/2 were performed for five fatty acid esters LH I -V Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported the analysis of SQOOH isomers in human SSLs by using LC−MS/MS with atmospheric pressure chemical ionization (APCI), but due to the nature of APCI fragmentation, fragment ions with similar patterns were produced, making it difficult to selectively analyze SQOOH isomers . Thus, we recently developed an improved method that can selectively and sensitively analyze SQOOH isomers on the basis of evidence that the analysis of sodium adducts during LC−MS/MS analysis enables the selective analysis of other lipid hydroperoxide isomers . With the use of this method, we investigated the oxidation mechanisms of squalene and identified that singlet oxygen oxidation of squalene forms six SQOOH isomers in nearly equal amounts, whereas free radical oxidation mainly forms 2‐ and 3‐OOH‐SQ .…”
Section: Introductionmentioning
confidence: 99%